Preparation method of wave-absorbing polyaniline oriented induction MOF hollow carbon fiber
By using polyaniline to directed growth of MOF nanoparticles and carbonized on the surface of biomass tree cotton fibers, polyaniline to directed MOF@ hollow carbon fibers for absorption were prepared, which solved the problems of high production cost of carbon fibers and limited electromagnetic wave absorption performance in the prior art, and achieved efficient and economical electromagnetic wave absorption effect.
Patent Information
- Application Number
- CN202411761137.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The existing carbon fiber and its composite materials preparation technology for electromagnetic absorption have high costs, complex processes, and mismatch of non-magnetic materials and electromagnetic wave input impedances, resulting in limited electromagnetic wave absorption performance.
Biomass tree cotton fibers were used as carbon templates, and MOF nanoparticles were grown on the surface through polyaniline orientation induction method, and combined with carbonization treatment, polyaniline orientation inducing MOF@ hollow carbon fibers for absorbing wave were prepared.
The preparation of light-weight broadband electromagnetic wave absorbing materials has been realized, the economic value of tree cotton biomass fiber has been enhanced, and functional application has excellent electromagnetic absorption performance.
Smart Images

Figure CN119571504A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of carbon fiber materials and composite materials thereof, and specifically relates to a method for preparing polyaniline directional induced MOF@ hollow carbon fiber for wave absorption. Background Art
[0002] The development of efficient and high-potential electromagnetic functional materials has become one of the research focuses to promote the management of electromagnetic energy attenuation. Among them, the use of absorbing materials to absorb electromagnetic waves or the use of electromagnetic shielding materials to reflect electromagnetic waves are the two most common electromagnetic functional materials for eliminating and reducing electromagnetic radiation. Among them, advanced carbon materials have been reported as the most attractive electromagnetic attenuation materials due to their rich functional groups, stronger electrical loss and considerable dielectric loss. So far, the research on the preparation methods of many carbon materials has flourished. Unfortunately, the synthetic products of these carbon materials are single forms, which require expensive raw materials and complex processes. Therefore, we urgently need to provide sustainable and economical raw materials and simple synthesis technologies for the production of multifunctional carbon materials. Biomass (pumpkin seed shells, walnut shells, egg shells, orange peels, etc.) is a renewable resource with a wide source, low cost, and does not increase the content of atmospheric CO2. It can be seen that biomass-derived carbon materials are green and environmentally friendly materials. They have many advantages such as wide sources, environmentally friendly and renewable, unique self-structure, and low cost. They have been widely used in electrode materials, electrocatalysis, adsorption and other fields.
[0003] MOF electromagnetic functional materials have received extensive attention in the electromagnetic field due to the following reasons: First, the multifaceted microstructures and components of the MOF structure can be easily adjusted to tune the electromagnetic parameters and accelerate energy absorption and dissipation. Second, the self-template transformation method takes into account the atomic-level distribution of magnetic metal sources and organic ligands, which provides the possibility of preparing EMW absorbers with dielectric multi-loss capabilities. Third, the hierarchical porous structure of MOF-derived materials provides the lightness of the absorber, excellent impedance matching characteristics, and multiple reflection and scattering paths. Therefore, innovative work on MOF-based electromagnetic functional materials has been widely developed, and their absorption properties are constantly being updated. Summary of the invention
[0004] The purpose of the present invention is to solve the above-mentioned problems existing in the existing preparation technology of carbon fiber and composite materials for electromagnetic absorption, and to provide a preparation method of polyaniline directional induced MOF@ hollow carbon fiber for electromagnetic absorption.
[0005] A preparation method of polyaniline directional induced MOF@hollow carbon fiber for microwave absorption is achieved by the following steps:
[0006] 1. Surface pretreatment of tree cotton fiber: soak the tree cotton fiber in anhydrous ethanol, then add aniline and stir, then drop ammonium persulfate aqueous solution and continue stirring, wash and dry to obtain the tree cotton fiber loaded with polyaniline;
[0007] 2. Growth of MOF particles: The above-mentioned cotton fiber loaded with polyaniline is immersed in a methanol solution of dimethylimidazole and allowed to stand, and then a methanol solution of cobalt nitrate hexahydrate is added and allowed to stand for a long time, and then washed and dried to obtain cotton fiber with MOF particles grown thereon;
[0008] 3. Carbonization treatment: The tree cotton fiber on which the MOF particles are grown is calcined at high temperature in an inert gas atmosphere, and after being cooled in the furnace, the microwave-absorbing polyaniline directional induced MOF@hollow carbon fiber is obtained, thus completing the preparation method.
[0009] Furthermore, the hollowness of the tree cotton fiber in step 1 is 85% to 90%, the fiber length is 31 mm to 35 mm, and the fiber fineness is 16 μm to 28 μm.
[0010] Furthermore, the specific process of the surface pretreatment of the tree cotton fiber in step 1 is as follows: 0.4-0.6 g of tree cotton fiber is soaked in 100-500 ml of anhydrous ethanol, then 0.1-1 ml of aniline is added and stirred for 0.5-6 hours, and then 10-30 ml of ammonium persulfate aqueous solution is added dropwise and stirring is continued for 5-10 hours. After washing with anhydrous ethanol for 2-3 times, vacuum drying is performed at 60-80° C. for 15-24 hours to obtain tree cotton fiber loaded with polyaniline.
[0011] Furthermore, the concentration of the ammonium persulfate aqueous solution is 0.003-0.3 g / mL.
[0012] Furthermore, the methanol solution of dimethylimidazole in step 2 is as follows: 1 to 10 g of dimethylimidazole is added to 50 to 150 mL of anhydrous methanol and stirred thoroughly to dissolve, thereby obtaining a methanol solution of dimethylimidazole.
[0013] Furthermore, the standing time in step 2 is 24 hours.
[0014] Furthermore, the methanol solution of cobalt nitrate hexahydrate in step 2 is as follows: 1 to 5 g of cobalt nitrate hexahydrate is added to 50 to 150 mL of anhydrous methanol and stirred thoroughly to dissolve, thereby obtaining a methanol solution of cobalt nitrate hexahydrate.
[0015] Furthermore, the time for continuing to stand in step 2 is 24 hours.
[0016] Furthermore, the washing and drying in step 2 are as follows: washing with anhydrous methanol and anhydrous ethanol for 1 to 3 times respectively, and then drying at 60°C.
[0017] Furthermore, the growth of the MOF particles in step 2 can also be as follows: immersing the tree cotton fiber loaded with polyaniline in a deionized water solution of dimethylimidazole and letting it stand, then adding it to an aqueous solution of ferric chloride hexahydrate and continuing to let it stand, washing and drying, to obtain tree cotton fibers with grown MOF particles; the deionized water solution of dimethylimidazole: adding 1 to 10 g of dimethylimidazole to 100 mL of deionized water and stirring thoroughly to dissolve; the aqueous solution of ferric chloride hexahydrate: adding 1 to 5 g of ferric chloride hexahydrate to 25 mL of deionized water and stirring thoroughly to dissolve.
[0018] Furthermore, the growth of the MOF particles in step 2 can also be as follows: immersing the tree cotton fiber loaded with polyaniline in a methanol solution of dimethylimidazole and letting it stand, then adding a methanol solution of zinc nitrate hexahydrate and continuing to let it stand, washing and drying, to obtain tree cotton fibers with grown MOF particles; the methanol solution of dimethylimidazole: adding 1 to 10 g of dimethylimidazole to 100 mL of methanol and stirring thoroughly to dissolve; the methanol solution of zinc nitrate hexahydrate: adding 1 to 5 g of zinc nitrate hexahydrate to 100 mL of methanol and stirring thoroughly to dissolve.
[0019] Furthermore, the specific process of the carbonization treatment in step three is: putting the tree cotton fiber growing MOF particles into a tubular furnace, heating it to 625°C at a rate of 0.5-1.5°C / min under an inert gas atmosphere and keeping it warm for 45-175min; the inert gas is nitrogen or argon.
[0020] The present invention uses biomass materials as carbon templates and uses polyaniline as a directional guiding agent to precisely and controllably grow MOF nanoparticles on its surface. The carbonization process is precisely regulated, and composite component screening and optimization are performed, and electromagnetic parameters are regulated to optimize electromagnetic wave absorption characteristics. The present invention aims to promote the multifunctional application of natural fibers while optimizing the physical and chemical properties of carbon-based materials. This invention will have broad application prospects.
[0021] The reaction principle of the present invention is: tree cotton is a natural biomass fiber with an ultra-high aspect ratio and a unique hollow microscopic morphology. Biomass is the most abundant carbon source material other than petrochemical-based materials. In the context of the "dual carbon" goal, in addition to reasonably reducing the use of carbon-containing fossil fuels, thinking about how to fix the carbon dioxide gas absorbed by plants from the atmosphere through photosynthesis in a more stable form for a long time and making high-value use of it has become an important topic worthy of in-depth research. With the increasing complexity of scenarios such as commercial, radar monitoring, and military applications, researchers have gradually deepened their exploration of electromagnetic absorption materials. After carbonization, tree cotton fibers become carbon fibers with a unique hollow structure, which is conducive to electromagnetic absorption. First, hollow carbon can expand the propagation path of electromagnetic waves in the structure, providing more opportunities for multiple reflections and multiple scattering, thereby increasing energy attenuation and causing electromagnetic wave dissipation; second, the pores and gaps between hollow carbon fiber materials will introduce air, reduce the effective dielectric constant, and thus optimize impedance matching; third, the porosity of the hollow carbon fiber can act as a point defect, leading to the appearance of a dipole moment, which enhances dielectric relaxation by improving the dielectric dipole polarization of the material, which is beneficial to the absorption of electromagnetic waves; fourth, the hollow porous structure can cause multipolarization relaxation and improve electromagnetic absorption performance. Therefore, tree cotton-derived carbon fiber materials have great application prospects in electromagnetic functional materials. However, since biomass-derived carbon materials are usually non-magnetic, the uniqueness of the electromagnetic wave attenuation mechanism and the mismatch of the electromagnetic wave input impedance seriously hinder their electromagnetic wave absorption performance. Therefore, tree cotton fiber is selected as a biomass template for subsequent carbonization treatment to obtain hollow carbon tube fibers. Polyaniline (PANI) has the advantages of light weight, corrosion resistance, easy preparation, and excellent dielectric properties, and is a reasonable choice for improving EM absorption performance. During the doping process, polyaniline H + and counter anions (such as Cl -, sulfate, phosphate) will not change. These polarities and dipoles are delocalized from the P bonds of the entire molecular chain, so polyaniline has higher conductivity and is considered to be one of the most promising candidate materials due to its excellent properties (including light weight, corrosion resistance, easy synthesis and dielectric loss capacity). At the same time, the amino groups on polyaniline can bond with the hydroxyl groups on the tree cotton fiber, thereby attracting the attachment of polyaniline. Therefore, binary composites with polyaniline with higher conductivity on the surface of hollow carbon fibers can adjust electromagnetic parameters and enhance electromagnetic absorption. Adding MOF particles on this basis can further enhance the electromagnetic absorption capacity of the material, because MOF particles, as a new type of porous material, have great application potential in the field of electromagnetic wave absorption due to their unique structural characteristics. Its large pore size and high specific surface area provide ample space for the absorption of electromagnetic waves, while its adjustable structural components make it possible to achieve customized design for specific functions. At the same time, the metal ions in the MOF particles can bond with the amino groups of polyaniline to produce metal chelation, thereby achieving directional induction of polyaniline, promoting the growth of MOF particles on the surface of tree cotton-derived hollow carbon fibers, achieving ternary composites, adjusting electromagnetic parameters, and accelerating energy absorption and dissipation.
[0022] The beneficial effect of the present invention is that it can combine the advantages of excellent magnetic loss electromagnetic wave absorption capacity of MOF-derived magnetic metal / C nanoparticles. Magnetic metal / carbon nanocomposites with various nanostructures are prepared by directly pyrolyzing MOF particles containing Fe / Co / Zn, such as zeolite imidazolate framework (ZIF-67) particles and biomass-derived carbon materials. These magnetic nanocomposites have the advantages of porous structure, high specific surface area and ferromagnetism. At the same time, the synergistic electromagnetic dissipation effect between the carbon-based and magnetic metal nanoparticles makes it a lightweight broadband electromagnetic wave absorption material. The carbon-based material prepared by the present invention has high hollowness, light weight, simple preparation method and easy process control. The economic value of tree cotton biomass fiber is enhanced while giving it functional applications. The polyaniline directional induced MOF-derived metal particles @ hollow carbon composite fiber prepared by the present invention. It can show specificity in chemical and physical (thermal, optical, electromagnetic, etc.) properties.
[0023] The invention is suitable for the preparation of polyaniline directional induced MOF@hollow carbon fiber for wave absorption. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a SEM image of the polyaniline directional induced MOF@hollow carbon fiber for wave absorption prepared in Example 1;
[0025] Figure 2 This is a 3D loss diagram of electromagnetic absorption performance of the directional induced MOF@hollow carbon fiber prepared by polyaniline for absorbing waves in Example 1;
[0026] Figure 3 This is a SEM image of the polyaniline directional induced MOF@hollow carbon fiber for wave absorption prepared in Example 2;
[0027] Figure 4 This is a 3D loss diagram of electromagnetic absorption performance of the polyaniline directional induced MOF@hollow carbon fiber prepared in Example 2;
[0028] Figure 5 This is a 3D loss diagram of the electromagnetic absorption performance of the polyaniline-loaded hollow carbon fiber prepared in Example 3. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.
[0030] Specific implementation method 1: This implementation method is a preparation method of polyaniline directional induced MOF@hollow carbon fiber for microwave absorption, which is achieved by the following steps:
[0031] 1. Surface pretreatment of tree cotton fiber: soak the tree cotton fiber in anhydrous ethanol, then add aniline and stir, then drop ammonium persulfate aqueous solution and continue stirring, wash and dry to obtain the tree cotton fiber loaded with polyaniline;
[0032] 2. Growth of MOF particles: The above-mentioned cotton fiber loaded with polyaniline is immersed in a methanol solution of dimethylimidazole and allowed to stand, and then a methanol solution of cobalt nitrate hexahydrate is added and allowed to stand for a long time, and then washed and dried to obtain cotton fiber with MOF particles grown thereon;
[0033] 3. Carbonization treatment: The tree cotton fiber on which the MOF particles are grown is calcined at high temperature in an inert gas atmosphere, and after being cooled in the furnace, the microwave-absorbing polyaniline directional induced MOF@hollow carbon fiber is obtained, thus completing the preparation method.
[0034] In the tree cotton fiber loaded with polyaniline in step 1 of this embodiment, the loaded polyaniline is used as the rivet site of the MOF particle to achieve its directional and controllable growth.
[0035] The polyaniline directional induced MOF@hollow carbon fiber for wave absorption prepared in step three of this embodiment is used for electromagnetic wave absorption function applications.
[0036] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the hollowness of the tree cotton fiber in step 1 is 85% to 90%, the fiber length is 31mm to 35mm, and the fiber fineness is 16μm to 28μm. Other steps and parameters are the same as those in specific implementation method 1.
[0037] Specific implementation method three: This implementation method is different from specific implementation method two in that the specific process of the surface pretreatment of the tree cotton fiber in step one is as follows: 0.4-0.6g of tree cotton fiber is soaked in 100-500ml of anhydrous ethanol, then 0.1-1ml of aniline is added and stirred for 0.5-6h, then 10-30ml of ammonium persulfate aqueous solution is added dropwise and stirred for 5-10h, after washing with anhydrous ethanol for 2-3 times, vacuum drying is performed at 60-80°C for 15-24h to obtain tree cotton fiber loaded with polyaniline. The other steps and parameters are the same as those in specific implementation method two.
[0038] Specific embodiment 4: This embodiment is different from specific embodiment 3 in that the concentration of the aqueous ammonium persulfate solution is 0.003-0.3 g / mL. Other steps and parameters are the same as those of specific embodiment 3.
[0039] Specific embodiment 5: This embodiment is different from specific embodiment 1 in that the methanol solution of dimethylimidazole in step 2 is: 1-10 g of dimethylimidazole is added to 50-150 mL of anhydrous methanol and stirred to dissolve to obtain a methanol solution of dimethylimidazole. Other steps and parameters are the same as those in specific embodiment 1.
[0040] Specific implementation method 6: This implementation method is different from the specific implementation method 1 in that the standing time in step 2 is 24 hours. The other steps and parameters are the same as those in the specific implementation method 1.
[0041] Specific embodiment 7: This embodiment is different from specific embodiment 1 in that the methanol solution of cobalt nitrate hexahydrate in step 2 is: 1-5 g of cobalt nitrate hexahydrate is added to 50-150 mL of anhydrous methanol and stirred to dissolve, to obtain a methanol solution of cobalt nitrate hexahydrate. Other steps and parameters are the same as those in specific embodiment 1.
[0042] Specific implementation example eight: This implementation example is different from specific implementation example one in that the time for continuing to stand in step two is 24 hours. The other steps and parameters are the same as those of specific implementation example one.
[0043] Specific embodiment 9: This embodiment is different from specific embodiment 1 in that the washing and drying in step 2 are performed by washing with anhydrous methanol and anhydrous ethanol for 1 to 3 times respectively, and then drying at 60° C. The other steps and parameters are the same as those in specific embodiment 1.
[0044] Specific embodiment ten: This embodiment is different from the specific embodiment one in that the growth of the MOF particles in step two can also be: immersing the tree cotton fiber loaded with polyaniline in a deionized aqueous solution of dimethylimidazole and letting it stand, then adding it to an aqueous solution of ferric chloride hexahydrate and continuing to stand, washing and drying, to obtain the tree cotton fiber with grown MOF particles;
[0045] The deionized water solution of dimethylimidazole: add 1-10 g of dimethylimidazole into 100 mL of deionized water and stir thoroughly to dissolve;
[0046] The aqueous solution of ferric chloride hexahydrate: add 1-5 g of ferric chloride hexahydrate into 25 mL of deionized water and stir thoroughly to dissolve.
[0047] The other steps and parameters are the same as those in the first embodiment.
[0048] Specific embodiment 11: This embodiment is different from the specific embodiment 1 in that the growth of the MOF particles in step 2 can also be: immersing the tree cotton fiber loaded with polyaniline in a methanol solution of dimethylimidazole and letting it stand, then adding a methanol solution of zinc nitrate hexahydrate and continuing to stand, washing and drying, to obtain the tree cotton fiber with the MOF particles grown;
[0049] The methanol solution of dimethylimidazole: add 1-10 g of dimethylimidazole into 100 mL of methanol and stir thoroughly to dissolve;
[0050] The methanol solution of zinc nitrate hexahydrate: add 1-5 g of zinc nitrate hexahydrate into 100 mL of methanol and stir thoroughly to dissolve.
[0051] The other steps and parameters are the same as those in the first embodiment.
[0052] Specific embodiment 12: This embodiment is different from specific embodiment 1 in that the specific process of carbonization treatment in step 3 is as follows: the tree cotton fiber with MOF particles is placed in a tubular furnace, and heated to 625°C at a rate of 0.5-1.5°C / min under an inert gas atmosphere and kept warm for 45-175min; the inert gas is nitrogen or argon. The other steps and parameters are the same as those in specific embodiment 1.
[0053] The beneficial effects of the present invention are verified by the following examples:
[0054] Embodiment 1:
[0055] A preparation method of polyaniline directional induced MOF@hollow carbon fiber for microwave absorption is achieved by the following steps:
[0056] 1. Surface pretreatment of tree cotton fiber: soak the tree cotton fiber in anhydrous ethanol, then add aniline and stir, then drop ammonium persulfate aqueous solution and continue stirring, wash and dry to obtain the tree cotton fiber loaded with polyaniline;
[0057] 2. Growth of MOF particles: The above-mentioned cotton fiber loaded with polyaniline is immersed in a methanol solution of dimethylimidazole and allowed to stand, and then a methanol solution of cobalt nitrate hexahydrate is added and allowed to stand for a long time, and then washed and dried to obtain cotton fiber with MOF particles grown thereon;
[0058] 3. Carbonization treatment: The tree cotton fiber on which the MOF particles are grown is calcined at high temperature in an inert gas atmosphere, and after being cooled in the furnace, the microwave-absorbing polyaniline directional induced MOF@hollow carbon fiber is obtained, thus completing the preparation method.
[0059] The hollowness of the tree cotton fiber in step 1 of this embodiment is 85% to 90%, the fiber length is 31 mm to 35 mm, and the fiber fineness is 16 μm to 28 μm;
[0060] The specific process of the surface pretreatment of the tree cotton fiber in step 1 is as follows: 0.5 g of the tree cotton fiber is soaked in 200 ml of anhydrous ethanol, 0.4 ml of aniline is added and stirred for 2 hours, 20 ml of ammonium persulfate aqueous solution is added dropwise and stirring is continued for 5 to 10 hours, after washing with anhydrous ethanol for 2 to 3 times, vacuum drying at 60 to 80° C. for 15 to 24 hours, to obtain the tree cotton fiber loaded with polyaniline;
[0061] The concentration of the ammonium persulfate aqueous solution is 0.0125 g / mL;
[0062] The methanol solution of dimethylimidazole in step 2: add 4 g of dimethylimidazole to 120 mL of anhydrous methanol and stir thoroughly to dissolve, to obtain a methanol solution of dimethylimidazole;
[0063] The standing time in step 2 is 24 hours;
[0064] The methanol solution of cobalt nitrate hexahydrate in step 2: add 3.87 g of cobalt nitrate hexahydrate into 120 mL of anhydrous methanol and stir thoroughly to dissolve, to obtain a methanol solution of cobalt nitrate hexahydrate;
[0065] The time for continuing to stand in step 2 is 24 hours;
[0066] Washing and drying in step 2: washing twice with anhydrous methanol and anhydrous ethanol respectively, and then drying at 60°C;
[0067] The specific process of the carbonization treatment in step 3 is as follows: the tree cotton fiber with grown MOF particles is placed in a tubular furnace, and the temperature is raised to 625° C. at a rate of 1° C. / min under an inert gas atmosphere and kept warm for 120 min; the inert gas is argon.
[0068] Embodiment 2:
[0069] The differences between this embodiment and embodiment 1 are as follows: 0.1 ml of aniline is added in step 1; the concentration of the ammonium persulfate aqueous solution is 0.0031 g / mL; and the rest is the same as embodiment 1.
[0070] Embodiment 3:
[0071] The polyaniline-loaded cotton fiber prepared in step 1 of Example 2 was placed in a tubular furnace, and heated to 625° C. at a rate of 1° C. / min and kept at this temperature for 120 min in an inert gas atmosphere; the inert gas was argon.
[0072] In this embodiment, polyaniline-loaded hollow carbon fibers were prepared.
[0073] result:
[0074] from Figure 1 The SEM image of the polyaniline oriented MOF@hollow carbon fiber prepared in Example 1 shows that the carbon fiber morphology prepared after carbonization replicates the hollow morphology of tree cotton. The fiber diameter is ~15μm, the carbon wall thickness is about ~600nm, and MOF particles are successfully grown inside the hollow carbon tube by the method of this example, and Co metal oxide particles derived from MOF particles are grown on the surface and inside.
[0075] from Figure 2 From the 3D loss diagram of the electromagnetic absorption performance of the polyaniline directional induced MOF@hollow carbon fiber prepared in Example 1, it can be seen that the composite carbon fiber prepared by the method of this example has a reflection loss value of -56dB, and is an excellent electromagnetic absorption material.
[0076] from Figure 3 The SEM image of the polyaniline oriented MOF@hollow carbon fiber prepared in Example 2 shows that the carbon fiber morphology prepared after carbonization replicates the hollow morphology of tree cotton. The fiber diameter is ~15μm, the carbon wall thickness is about ~600nm, and MOF particles are successfully grown inside the hollow carbon tube by the method of this embodiment, and Co metal oxide particles derived from MOF particles are grown on the surface and inside.
[0077] from Figure 4 From the 3D loss diagram of the electromagnetic absorption performance of the polyaniline directional induced MOF@hollow carbon fiber prepared in Example 2, it can be seen that the composite carbon fiber prepared by the method of this example has a reflection loss value of -59dB, and is an excellent electromagnetic absorption material.
[0078] Figure 5 3D loss diagram of the electromagnetic absorption performance of the polyaniline-loaded hollow carbon fiber prepared in Example 3; compared with the polyaniline-oriented induced MOF@hollow carbon fiber prepared in Example 1, it increased by two times.
[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing polyaniline directional induced MOF@ hollow carbon fiber for microwave absorption, characterized in that It proceeds as follows:
1. Surface pretreatment of tree cotton fiber: soak the tree cotton fiber in anhydrous ethanol, then add aniline and stir, then drop ammonium persulfate aqueous solution and continue stirring, wash and dry to obtain the tree cotton fiber loaded with polyaniline; 2. Growth of MOF particles: The above-mentioned cotton fiber loaded with polyaniline is immersed in a methanol solution of dimethylimidazole and allowed to stand, and then a methanol solution of cobalt nitrate hexahydrate is added and allowed to stand for a long time, and then washed and dried to obtain cotton fiber with MOF particles grown thereon; 3. Carbonization treatment: The tree cotton fiber on which the MOF particles are grown is calcined at high temperature in an inert gas atmosphere, and after being cooled in the furnace, the microwave-absorbing polyaniline directional induced MOF@hollow carbon fiber is obtained, thus completing the preparation method.
2. The method for preparing a microwave absorbing polyaniline directional induced MOF@ hollow carbon fiber according to claim 1, characterized in that The hollowness of the tree cotton fiber described in step 1 is 85% to 90%, the fiber length is 31mm to 35mm, and the fiber fineness is 16μm to 28μm.
3. The method for preparing a microwave absorbing polyaniline directional induced MOF@hollow carbon fiber according to claim 1, characterized in that The specific process of the surface pretreatment of the tree cotton fiber in step 1 is as follows: 0.4-0.6 g of tree cotton fiber is soaked in 100-500 ml of anhydrous ethanol, then 0.1-1 ml of aniline is added and stirred for 0.5-6 hours, and then 10-30 ml of ammonium persulfate aqueous solution is added dropwise and stirred for 5-10 hours. After washing with anhydrous ethanol for 2-3 times, vacuum drying is performed at 60-80° C. for 15-24 hours to obtain tree cotton fiber loaded with polyaniline.
4. The method for preparing a microwave absorbing polyaniline directional induced MOF@hollow carbon fiber according to claim 3, characterized in that The concentration of the ammonium persulfate aqueous solution is 0.003-0.3 g / mL.
5. The method for preparing a microwave absorbing polyaniline directional induced MOF@ hollow carbon fiber according to claim 1, characterized in that The methanol solution of dimethylimidazole in step 2: add 1-10 g of dimethylimidazole into 50-150 mL of anhydrous methanol and stir thoroughly to dissolve, to obtain a methanol solution of dimethylimidazole.
6. The method for preparing a microwave absorbing polyaniline directional induced MOF@hollow carbon fiber according to claim 1, characterized in that The standing time in step 2 is 24 hours.
7. The method for preparing a microwave absorbing polyaniline directional induced MOF@hollow carbon fiber according to claim 1, characterized in that The methanol solution of cobalt nitrate hexahydrate in step 2: add 1 to 5 g of cobalt nitrate hexahydrate into 50 to 150 mL of anhydrous methanol and stir thoroughly to dissolve, thereby obtaining a methanol solution of cobalt nitrate hexahydrate.
8. The method for preparing a microwave absorbing polyaniline directional induced MOF@hollow carbon fiber according to claim 1, characterized in that The time for continuing to stand still in step 2 is 24 hours.
9. The method for preparing a microwave-absorbing polyaniline directional induced MOF@hollow carbon fiber according to claim 1, characterized in that Washing and drying in step 2: washing with anhydrous methanol and anhydrous ethanol for 1 to 3 times respectively, and then drying at 60°C.
10. The method for preparing a microwave absorbing polyaniline directional induced MOF@hollow carbon fiber according to claim 1, characterized in that The specific process of the carbonization treatment in step three is as follows: the tree cotton fiber with grown MOF particles is placed in a tubular furnace, and in an inert gas atmosphere, the temperature is raised to 625°C at a rate of 0.5-1.5°C / min and kept warm for 45-175min; the inert gas is nitrogen or argon.
Citation Information
Patent Citations
Wave-absorbing material derived from NiCo-MOF / biomass cotton and preparation method thereof
CN113912038A
Biomass-based silicon carbide composite fiber, preparation method thereof and electromagnetic absorption material
CN116084161A
MOF-derived wood-based porous carbon wave-absorbing material and preparation method thereof
CN116605863A